PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN KANTOR POS CABANG UTAMA KOTA SURABAYA - Ika Korika Swasti; Nur Fadila Rosida (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
Human resource in a company is essential as the main mover in determining the goal as well assisting to compete in an increasingly competitive business world. Dividing the workload on every organizational activity, dividing the workload on every employee, or dividing the workload on important office holder in organization equally can create a conducive work environment. Furthermore, it can make the work environment become more comfortable and safe. The objective of the study was to determine the effect of workload and work environment on employee work environment at Kantor Pos Cabang Utama Surabaya city with 59 employees as samples. In addition, the data collection was by distributing questionnaires with a Likert scale from 1 to 5. The study used a quantitative approach with Smart PLS analysis tool. The study found that factors such as workload and employee work environment determined 56.92% of employee performance, while other factors accounted for 43.08%.